DIRECTIONS OF INSTITUTIONAL REGULATION OF ECONOMIC SECURITY OF UKRAINE - RUZHYTSKYI, IHOR (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The relevance of the study of institutional support of economic security is proved. The results of the analysis revealed that in Ukraine today there is no coordinated mechanism for regulating economic security, regulators operate on a centralized model, organizational structure and functional system does not meet the requirements of economic security. The strategic directions of neutralization of conflict situations and harmonization of interests of subjects of maintenance of economic safety which provide: change of a paradigm of development from technocratic to ecologically safe are substantiated; formation of an effective mechanism for regulating economic security through a rational combination of market and state levers of influence aimed at anticipating and preventing threats; optimization of institutional support for economic security. Institutionalization of the process of ensuring economic security includes the involvement of a wide range of participants, along with their own goals and their inherent functions. Functioning depends on the following characteristics of economic dynamics: material needs, economic landmarks and interests, the motivation for economic activity determined under their influence. First of all, the subjects of economic security are the legislative, executive and judicial authorities within their statutory powers. Institutionalization of the process of ensuring economic security includes the involvement of a wide range of participants, along with their own goals and their inherent functions. Functioning depends on the following characteristics of economic dynamics: material needs, economic landmarks and interests, the motivation for economic activity determined under their influence. First of all, the subjects of economic security are the legislative, executive and judicial authorities within their statutory powers. At the second level, the so-called level of "secondary institutionalization", the role of the subject of economic security is played by ministries, departments, services and agencies, which are responsible for the actual implementation of economic security in the country. And at the last, third level are the structural units of the above departments, which are directly responsible for various areas of economic security. The strategic directions of neutralization of conflict situations and harmonization of interests of subjects of maintenance of economic safety which provide: change of a paradigm of development from technocratic to ecologically safe are substantiated; formation of an effective mechanism for regulating economic security through a rational combination of market and state levers of influence aimed at anticipating and preventing threats; optimization of institutional support of economic security in Ukraine.
Keywords: economy; economic security; institutional regulation; provision; strategic directions; institutes